Effect of purified Calotropis gigantea latex protease on the cheese quality - Shrestha, Nabindra Kumar; Maskey, Bunty (Tribhuvan University Journal of Food Science and Technology, 2023)
Cheesemaking has been relying solely on chymosin for so long. But factors like increased cheese production, diminishing supply of chymosin as well as religious and dietary limitations have been hindering the demand-production balance of cheese in the world. Hence, the primary objective of this study was to utilize the three-phase partitioning (TPP) purified Calotropis gigantea latex protease in cheesemaking. The cheese prepared using purified protease was compared with chymosin cheese for physicochemical, sensorial, textural, and microbiological evaluation. The optimum conditions for purified protease from response surface methodology (RSM) analysis were 6.25 milk pH and 45℃ milk temperature. The physicochemical parameters (moisture content, protein, ash, calcium, salt content, and pH) of cheeses prepared from latex protease and chymosin were significantly different (p<0.05). The yield of latex protease cheese was significantly higher (p<0.05) than chymosin cheese. In terms of texture and aftertaste, the cheese made with latex protease had significantly lower (p<0.05) mean scores than chymosin cheese. Compared to chymosin cheese, the latex protease cheese had a generally inferior textural character, with significantly (p<0.05) lower values for hardness, chewiness, gumminess, cohesiveness, and resilience. The total viable count and Lactobacilli count of the cheeses produced with chymosin and latex protease showed a significant (p<0.05) difference. Hence, this study highlighted that the TPP purified C. gigantea latex protease could be used as a plant coagulant for cheesemaking.